2018
DOI: 10.1002/alr.22108
|View full text |Cite
|
Sign up to set email alerts
|

Management of long‐lasting phantosmia: a systematic review

Abstract: Despite increasing interest in the treatment of phantosmia and reports of successful therapies, there remains a paucity of data and lack of consensus regarding optimal management of this difficult condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Even more so than quantitative olfactory loss, qualitative disturbances provide a source of frustration for both the patient and the clinician. Evidence for prescribed treatment for qualitative disorders was limited to 7 studies in a previous systematic review for phantosmia 16 and evidence for self-help measures appears to be very limited. 17 Some patients are so severely affected that consideration has been given to surgical removal of the olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Even more so than quantitative olfactory loss, qualitative disturbances provide a source of frustration for both the patient and the clinician. Evidence for prescribed treatment for qualitative disorders was limited to 7 studies in a previous systematic review for phantosmia 16 and evidence for self-help measures appears to be very limited. 17 Some patients are so severely affected that consideration has been given to surgical removal of the olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Phantosmia was classified as a qualitative disturbance of smell function and during the COVID-19 pandemic, this phenomenon was not reported. Phantosmia occurs due to a number of etiologies, including chronic rhinosinusitis, cranial trauma, intracranial hemorrhage, epilepsy, psychiatric conditions, brain radiotherapy, neurologic disorders, iatrogenic causes, and neurologic and neurodegenerative disorders and conductive or sensorineural pathophysiology of this specific symptom is still unclear [1]. The frequency of phantosmia has been reported by up to 25% in patients with odor disorder, and the incidence is higher in the elderly compared to the young population [3].…”
Section: Discussionmentioning
confidence: 99%
“…Phantosmia has been described as a sense of smell without a true stimulating odor and is a subjective olfactory dysfunction. Olfactory hallucinations have been previously associated with migraine typed headaches, endoscopic skull base surgery, intracranial tumors, brain radiotherapy treatment, and head trauma in the literature [1]. As described in the literature, phantosmia can persist for years.…”
Section: Introductionmentioning
confidence: 95%
“…With regard to phantosmia, various modalities have been trialled, including haloperidol, sodium valproate, phenytoin, topiramate, verapamil, nortriptyline, gabapentin, topical cocaine, transcranial magnetic stimulation and surgical excision of the olfactory mucosa. A recent systematic review of the current literature concluded, however, that there was insufficient evidence or consensus to make recommendations on the management of this condition [ 29 ]. Of interest, the successful treatment cases described in this review generally involved longer time periods than the present study (from 18 months to 11 years).…”
Section: Discussionmentioning
confidence: 99%